Trazabilidad microbiológica de enterobacterias en sitios poco monitoreados y contaminados con arsénico proveniente de fuentes naturales entre los 3600 y 3700 m.s.n.m en la parroquia de Toacaso - Rueda Santo, Tatiana Lisseth (2022)
The presence of arsenic in water has become into a global problem because millions of people are exposed to arsenic when they drink water and for agricultural purposes. This research aims to establish microbiological traceability of enterobacteria in poorly monitored contaminated sites with arsenic from natural sources between 3,600 and 3,700 m.o.s.l. in Toacaso parish, Talahuachana ravine at a point located at 3,623 m.a.s.l. coordinates -0.718646 south latitude and -78.733882 west longitude. On biophysical characterization of the area, the climate, temperature, precipitation and hydrogeology were considered. The results of physicochemical laboratory analyzes were compared with Ecuadorian regulations parameters. The relationship between the presence of enterobacteria and arsenic concentrations into water was carried out by bacterial cultures in Macconkey agar. The study area soil has volcanic origin with arsenic presence, under a cold temperate mesothermal climate, with moderate slopes and silty soils that facilitate arsenic mobility to lower altitude sites through precipitation, affecting arsenic concentrations and bacterial colonies. The physicochemical parameters of Talahuachana stream that exceed maximum permissible limits established at Ministerial Agreement 097 - A are manganese and dissolved oxygen, in the case of arsenic it exceeds the established concentrations by the World Health Organization and INEN 1108 sixth standard revision. Finally, the established relationship between enterobacteria and arsenic shows enterobacteria and other types of microorganisms are resistant to arsenic, according to observed characteristics at culture medium and Gram stain, possibly one of them belongs to Escherichia family, as well as other types of Gram negative bacteria. Concluding that water in Talahuachana stream should not be consumed by humans, nor for agricultural use due to its arsenic concentration and manganese that exceeds international and Ecuadorian standards, in addition to enterobacteria existence.